2021
DOI: 10.2147/jaa.s291333
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 Inhibits Proliferation and Migration of Airway Smooth Muscle Cells Induced by PDGF-BB Through miR-21/PTEN/Akt Axis

Abstract: Background LncRNA H19 expression is down-regulated in patients with asthma. The hyperplasia of airway smooth muscle cells (ASMCs) promotes the development of airway remodeling in asthma. Therefore, we attempted to evaluate the regulatory function of H19 in the proliferation and migration of ASMCs. Methods The expressions of H19 and miR-21 were detected using qRT-PCR. PDGF-BB-induced abnormal proliferation and migration of ASMCs was used as the airway remodeling model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…Our results demonstrated a role of H19 in the regulation of Orai1 expression and thus proliferation and migration of hBSMCs. Our results are contradictory to another study which showed that H19 inhibited platelet-derived growth factor (PDGF)-induced proliferation and migration of ASMCs [39]. H19 was also found to be decreased in ASMCs from patients with mild asthma when compared to healthy controls [57].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrated a role of H19 in the regulation of Orai1 expression and thus proliferation and migration of hBSMCs. Our results are contradictory to another study which showed that H19 inhibited platelet-derived growth factor (PDGF)-induced proliferation and migration of ASMCs [39]. H19 was also found to be decreased in ASMCs from patients with mild asthma when compared to healthy controls [57].…”
Section: Discussioncontrasting
confidence: 99%
“…The interaction between H19 and miR-93-5p was not studied previously, even that H19 has been reported to interact with multiple miRNAs to regulate diverse biological processes. In smooth muscle cells, H19 is shown to interact with miR-Let-7b and upregulate the expression angiotensin II type 1 receptor (AT 1 R) to promote pulmonary artery smooth muscle cell proliferation [17], interact with miR-21 to regulate the proliferation and migration of ASMCs [39], and interact with miR-599 to promote vascular smooth muscle cell proliferation [40]. In skeletal muscle, the only tissue with persistent H19 expression after birth, H19 was found to interact with miR-675-3p and miR-675-5p to promote skeletal muscle differentiation and regeneration [41].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of serum lncRNA KCNQ1OT1 can be used to monitor the occurrence and progression of airway remodeling in childhood asthma, thus providing a new idea and diagnostic tool for asthma therapy. LncRNA H19 overexpression reduces the growth and migration of platelet-derived growth factor-BB(PDGF-BB)-induced ASMCs by acting on miR-21/PTEN/Akt pathway, which can be used as a potential biomarker and therapeutic target for ASMCs proliferation [ 97 ]. The above results suggest that lncRNAs not only directly act on ASMCs, but also indirectly control miRNA target gene expression to regulate the growth and migration of ASMCs by interacting with miRNA.…”
Section: Lncrnas In Asthmamentioning
confidence: 99%
“… 14 lncRNA H19 was decreased in airways of asthmatics compared with healthy controls, 16 and lncRNA H19 overexpression was reported to inhibit proliferation and migration of airway smooth muscle cells. 21 However, its roles and mechanisms in airway epithelial cells in asthma are not reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Moreover, lncRNAs involved in airway diseases have also been widely reported. [16][17][18][19][20][21] LncRNAs in peripheral blood are differentially expressed between asthmatic patients and healthy controls, 22 and even between eosinophilic asthmatics and basophilic asthmatics. 23 LncRNA PVT1 was correlated with glucocorticoid resistance in severe asthmatics, and impacted proliferation of airway smooth muscle cells and release of inflammatory factor IL-6, which could be a therapy target for airway remodeling.…”
Section: Introductionmentioning
confidence: 99%